EFFECTS OF ASCORBIC ACID ON BLOOD MALONALDEHYDE (MDA) LEVEL TO FIND OUT ITS ANTI-PEROXIDATIVE POTENTIAL - Bandyopadhyay, Sayan; Kotal, Ritesh Sankar; Bhattacharya, Rupajit (Journal of Biomedical and Pharmaceutical Research, 2018)
Anti oxidants are classified into two broad divisions, depending on whether they are soluble in water (hydrophilic) or in lipids (hydrophobic). In general, water soluble antioxidants react with oxidants in the cell cytoplasm and the blood plasma, while lipid soluble antioxidants protect the cell membranes from lipid peroxidation. These compounds may be synthesized in the body r obtained from the diet. The amount of protection provided by any one antioxidant will also depends on its conc., its activity towards the particular reactive oxygen species being considered and the status of the antioxidants with which it interacts 2,3. Keywords: Anti oxidant metabolites, Cancer, Anti-diabetic etc. & Treatment and Management